Penguatan Literasi Numerasi melalui Kegiatan Pesantren Kilat pada Siswa Sekolah Dasar di Rawamangun, Jakarta Timur - Selly Anastassia Amellia Kharis; Sri Maulidia Permatasari; Sajida Humaira; Melisa Arisanty; Sri Sukatmi; Moh. Muzammil; Muhammad Firman Karim; Nurmala Pangaribuan (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2026)
Numeracy literacy is a fundamental competency that must be possessed by every child to support daily activities. It encompasses not only arithmetic skills but also the ability to understand, analyse, and apply mathematical concepts in real-life contexts. However, many students still show low interest and experience difficulties in relating numerical concepts to everyday problems. One effort to strengthen numeracy literacy is through pesantren kilat activities designed in an educational and contextual manner. This program integrates the reinforcement of religious values with mathematics numeracy learning. The objective of this activity is to improve numeracy literacy among elementary school students in Rawamangun, East Jakarta. The method employed was an educational game-based approach emphasizing active participation. Quantitatively, the average score of participants increased from 14.00 to 15.38, and paired sample t-test results indicated a significant improvement after the activity. Therefore, pesantren kilat can serve as effective alternative learning medium for enhancing numeracy literacy.